PENGARUH KEPEMIMPINAN KEPALA SEKOLAH DAN PROFESIONALISME GURU TERHADAP KINERJA GURU SEKOLAH DASAR NEGERI KECAMATAN SIAK KABUPATEN SIAK - Marliya Marliya; Gimin Gimin; Nurpit Junus (Jurnal JUMPED (Jurnal Manajemen Pendidikan), 2017)
The purpose of this study was to determine the direct and indirect effects ofschool leadership and professionalism of teachers on the performance of elementary school(SD) in Siak Districts Siak. This study uses a quantitative method using a technical of the pathanalysis. As for variables the study consisted of two independent variables that PrincipalLeadership (X1) and Teacher Professionalism (X2) while the dependent variable is the TeacherPerformance (Y). The study population was a teacher SDN districts of Siak regency Siakamounted to 188 people and 65 samples. The result of data analyses shown leadership ofheadmaster has given direct effect significantly trough teacher professionalism by 17,8%. Theother analyses shown that leadership of headmaster has given significant effect through teacherperformance by 6,65%, then leadership of headmaster and teacher professionalism throughteacher performance by 24,7% contribution. The result of data analyses shown that teacherprofessionalism has given significantly effect through teacher performance by 10,8%.